Internet and traditional media use and public opinion formation : a test of the assumptions of spiral of silence theory - Ahrari, Sadollah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This study has examined the assumptions of the Spiral of Silence Theory in the presence of Internet use variables on a probability sample of 312 undergraduate students of the University of Malaya. The study adopted cross-sectional research design using survey method. The respondents' own opinion, perception of current and future climates of opinion, and willingness to express own opinion were tapped on the controversial issue of using English as a medium for teaching Math and Science in schools in Malaysia, on a 7-point scale. The respondents' Internet usage, exposure to TV news and informational programs, and newspaper reading patterns also were measured at an ordinal level measurement. In addition, the data were collected on respondents' fear of isolation using a 10-item index on a 7-point scale. After the data preparation, the data were analyzed using SPSS software, and relevant statistical methods such as correlation, and linear regression were used to test the hypotheses of the study. Based on the Spiral of Silence and Internet use literature, six hypotheses were tested. It was hypothesized that traditional media use will relate with own opinion, opinion climate, and opinion expression. The study found a partial support for this hypothesis, with TV news & informational programs relating with own opinion and opinion expression, and newspaper reading relating with own opinion and opinion climate. In addition, of the four Internet use variables, blog use had a significant relationship with own opinion and opinion climate, and online news use related with opinion expression. Blog use also moderated the relationship between TV news & informational programs and opinion climate. Contrary to our expectation, opinion climate and fear of isolation variables had no relationship with opinion expression. The implications of these findings are discussed from the stand point of the conceptualization of the Spiral of Silence phenomena.